EFFICACY AND SAFETY OF DRUG-ELUTING BALLOONS (DEB) IN THE TREATMENT OF PATIENTS PRESENTED WITH ACUTE STEMI - JAN, MW; KHAN, SA; AKBAR, F; KHAN, N; RAHMAN, G; NASRULLAH, . (Biological and Clinical Sciences Research Journal, 2023)
Drug-eluting balloons (DEB) have emerged as a promising strategy for coronary revascularization, offering the capability to deliver anti-proliferative medicines directly to coronary arteries. Nevertheless, the exploration of their role in the acute STEMI context is now underway. Objective: To assess the efficacy of DEB in mitigating major adverse cardiac events (MACE) among individuals diagnosed with Acute ST-segment elevation myocardial infarction (STEMI) at the Peshawar Institute of Cardiology. The present study employed various methodologies to investigate the research question. A prospective cohort study was undertaken during a period spanning from September 2022 to June 2023, encompassing a sample size of 100 eligible participants. The study gathered data on the baseline characteristics of the participants, as well as the details of the DEB intervention. Additionally, safety outcomes were assessed and recorded. The study included statistical analyses to evaluate alterations in troponin and CK-MB levels following DEB intervention. During the follow-up period, many patient outcomes were documented, including MACE, occurrences of bleeding episodes, and instances of restenosis. The study's findings demonstrated noteworthy decreases in troponin and CK-MB levels following the DEB intervention, suggesting effective restoration of blood flow to the heart muscle. The study observed a significant decrease in troponin levels, from an initial mean of 12.7 ng/mL (±4.6) to a final mean of 5.3 ng/mL (±2.1) (p < 0.001). Similarly, CK-MB levels showed a significant reduction, with an initial mean of 42.3 U/L (±12.8) decreasing to a final mean of 20.5 U/L (±8.3) (p < 0.001). Nevertheless, there was a notable rise in MACE rates after the DEB intervention, as 38% of the individuals observed encountered MACE throughout the follow-up period. The safety concerns encompass hemorrhagic episodes, occurring in 10% of cases, and restenosis observed in 14% of cases. In conclusion, DEB has shown effectiveness in attaining myocardial reperfusion. However, the observed rise in MACE rates and safety concerns emphasize the intricate nature of DEB utilization in cases of acute STEMI. Additional investigation is required to enhance the process of selecting patients and refining procedure approaches within this particular environment.